Lower calyceal stone clearance after extracorporal shockwave lithotripsy (ESWL): prevalence and associated factors - Che Mohamed, Siti Kamariah; Kamarulzaman, Mohd Nazli; Hassan, Radhiana; Ghazali, Hamid (2014)
Introduction: Since its clinical introduction, extracorporeal shock wave lithotripsy (ESWL) has maintained an important role in the management of urinary calculi. The success of ESWL depends on the effective disintegration and evacuation of stone debris. The stone clearance rate differs for renal calculi at different sites, being the lowest for lower pole calyceal calculi. The low clearance rate for lower calyceal stones is more a problem of debris retention rather than stone fragmentation. The aim of this study is to find out the prevalence of stone clearance after ESWL for lower calyceal stones and relationship between the radiologic anatomy of the lower pole calyx (as seen on pre-operative IVU) and stone clearance. Study design: A retrospective analysis of patients with lower calyceal stones of 2cm or less in diameter which were treated with ESWL in HTAA from 2008 to 2011. The stone location and size were determined on plain abdominal radiograph. Radiographic anatomical factors were determined on pre-ESWL IVU, which were infundibulopelvic angle (IPA), infundibular length (IL) and width (IW). Patients were treated with ESWL using LT02X lithotripter machine, under intravenous or intramuscular analgesia. A stone-free status was defined as no evidence of fragments on plain radiograph 3 months after ESWL. All statistical analyses were performed with SPSS version 18.0.1 for Windows. Result Total of 14 patients that fulfill the criteria were included in the study; 10 (71.4%) patients were male and 2 (28.6%) patients were female. Majority of patients were Malays (85.7%). Age ranges from 20-70 years, but most of the patients were more than 40 years of age. Most of the patients have stone size of 1-2cm in sizes (85.7%), but the stone laterality was equal. For anatomical factors of the lower pole calyx, most of the patients showed wide infundibular pelvic angle (IPA), in which 64.3% had more than 40 degrees of angle. Majority had short infundibular length (IL), which was less than 30mm (85.7%). The infundibular width (IW) was also wide in most of the patients, as 92.9% had IW of more than 4mm. Stone clearance after ESWL was 71.4%. When measuring the predictors of outcome of stone clearance using Fishers exact test, there was no statistically significant in uence for all the anatomical factors tested. Conclusion It is important to assess the possible factors that can predict the probability of stone clearance after ESWL, as the most appropriate treatment modality for lower calyceal stones can accordingly be planned. However, statistically significant sample size cannot be achieved in this study due to multiple unavoidable circumstances. Longer duration of study with larger sample size should be carried out for more complete data review and accurate results.